STRATEGY AS A TOOL FOR ENSURING THE EFFICIENT FUNCTIONING OF THE ENTERPRISE - LUKIANOVA, Valentyna; HOLOVACH, Tetiana; ZAKRYZHEVSKA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The real sector of Ukraine’s economy is currently characterized by crisis phenomena that hold back the pace of its recovery. In this regard, focusing on short-term development programs, the absence or wrongly chosen strategy leads only to the localization of losses and to a decrease in the efficiency of enterprises in the long term. In turn, this necessitates the implementation of strategic management, which provides an opportunity for enterprises to ensure economic growth and get out of a crisis state. The article presents developments in the field of strategic management, highlights methodological problems of strategizing. Theoretical approaches to the formation of enterprise strategies are considered. It was established that the process of strategic management in Ukraine requires the use of modern technologies and tools. That is why there is a need to deepen research into the theoretical and methodological foundations of strategic management at all levels. The necessity of using the strategizing system as a tool for mobilizing internal reserves, taking into account external factors, forming and implementing strategies, promoting the development of the enterprise in the long term, is substantiated. By considering the stages of the process and strategizing tools, it is possible to conclude that the chosen strategy meets the goals, opportunities, and requirements of the enterprise’s external environment. To characterize the real (initial) strategic processes taking place at enterprises, it is necessary to take into account the peculiarities of different types of enterprises, their branch affiliation and competitive status. The initial strategic processes determine the individuality of the strategic choice of business processes for their further optimization, and the criteria for their selection are formed. Timely detection of problems and implementation of measures to adjust the process or content of strategy implementation, review of goals, is impossible without the use of strategic control, the key element of which is the system of indicators. This system should contain indicators that are control points for evaluating the effectiveness of strategy implementation at each stage. The presented control indicators are differentiated according to the main classification features.